Exopolysaccharide produced by the potential probiotic Lactococcus garvieae C47: Structural characteristics, rheological properties, bioactivities and impact on fermented camel milk. (15th December 2020) - Ayyash, Mutamed; Abu-Jdayil, Basim; Itsaranuwat, Pariyaporn; Almazrouei, Noora; Galiwango, Emmanuel; Esposito, Gennaro; Hunashal, Yamanappa; Hamed, Fathalla; Najjar, Zein
Highlights: Exopolysaccharide C47 has unique backbone structure. Exopolysaccharide C47 possesses remarkable bioactive properties. Exopolysaccharide C47 has a shear-thinning behavior. Rheological properties of fermented camel milk were investigated. Abstract: Fermented camel milk possesses a weak (liquid-like) gel structure. We aimed to 1) investigate the characteristics, bioactivities and rheological properties of the exopolysaccharide (EPS) produced by Lactococcus garvieae -C47 (exopolysaccharide-C47 product), a potential probiotic bacterium, on milk extracted from camels and 2) examine the rheological properties of the fermented camel milk produced by L. garvieae -C47. Exopolysaccharide-C47 product (molecular weight: 7.3 × 10 6 Da) was composed of the following monosaccharides: glucose (82.51%), arabinose (5.32%) and xylose (12.17%). The antioxidant, antitumor and α-amylase inhibitory activities of exopolysaccharide-C47 product reached up to 67.52, 59.35 and 91.0%, respectively. The apparent viscosity of exopolysaccharide-C47 product decreased with the increase in shear rate and declined by increasing the temperature up to 50 °C. The rheological properties of exopolysaccharide-C47 product are influenced by the salt type and pH value. The exopolysaccharide product produced by L. garvieae C47 possesses valuable health benefits and has the ability to improve the weak structure of fermented camel milk.